P155 Effects of upper airway muscle training on upper airway physiology in people with obstructive sleep apnea. (7th October 2021) - Wallace, E; Eckert, D; Osman, A; Naik, G; Carberry, J
Abstract: Introduction: Previous studies demonstrate that oropharyngeal exercises can reduce obstructive sleep apnoea (OSA) severity. However, the physiological mechanisms underlying this improvement are unknown. Thus, this study aimed to evaluate the effects of a speech-pathology led, targeted upper airway muscle training protocol on upper airway physiology. Methods: People with mild-moderate OSA (n=12 studied to date, 5 females, 7 males) completed 12 weeks of daily upper airway muscle training targeting the muscles of the tongue and soft palate. Pre- and post-training outcome measures included anterior and posterior tongue muscle strength and endurance and upper airway collapsibility via the upper airway collapsibility index. Results: Preliminary findings indicate that 12 weeks of targeted exercise training improved anterior and posterior tongue muscle strength, respectively (54.3±12.7 vs. 61.5±7.7kPa, p<0.01, 50.1±8.5 vs. 58.0±8.5kPa, p<0.01), and anterior and posterior tongue muscle endurance, respectively (15.7±10.9 vs. 24.1±8s, p<0.01, 9.5±4.2 vs. 23.3±17.7s, p<0.01). The upper airway collapsibility index improved post-training (25.5±18.9 vs. 12.26±12.11 %, p=0.03). Conclusions: Twelve weeks of upper airway muscle training improved tongue muscle strength, endurance and upper airway collapsibility in people with mild-moderate OSA. These physiological changes provide insight into the potential mechanisms mediating reductions in OSA severity with oropharyngeal exercises. This research was supported by the 2019 Phillips/ASA Sleep Research grant.